ГУМАНІСТИЧНИЙ ПІДХІД ДО ВИХОВНОГО ПРОЦЕСУ ТА АСПЕКТИ ВИХОВНОЇ СИСТЕМИ ВНЗ - Нємцева, Наталія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглядається гуманізація виховного процесу, що є базисом цілеспрямованої зміни особистості. Зазначається, що суттєвим моментом у виховному процесі технічного вузу є можливість забезпечення сучасної студентської молоді сприятливими умовами для використання її творчого потенціалу, допомога у визначенні й реалізації інтересів студентів та їх захоплень, намагання зробити студентське життя більш насиченим та цікавим, надання змоги вирішувати питання корпоративного значення на відповідному рівні. В статье рассматривается гуманизация воспитательного процесса, которая является базисом изменения личности. Отмечается, что существенным моментом в воспитательном процессе технического вуза является возможность обеспечения современной студенчиской молодежи благоприятными условиями для использования ее творческого потенциала, помощь в определении и реализации интересов студентов и их увлечений, попытки сделать студенческую жизнь более насыщенной и интересной. Humanization of educational process is searched in the paper. It is a basis for purposeful changes of personality. First of all humanism means humanity, love to people, high level of tolerance, gentleness in relationships, respect towards person and his dignity. The meaning of humanism is formed as system of value orientations and its main idea is declaration of a person as supreme value. It is admitted that vital point in educational process of technical university is an opportunity to provide modern young students with favourable conditions for application of their creative potential, help in determination and realization of students` interests and likings, attempts in making students life more eventful and interesting, give an opportunity to decide the corporative issues on a corresponding level. During educational process implementation of this principle means transfer from monologue of a teacher to his dialogue with students or pupil, equal in rights and kind communication of all its members, maximum consideration of student`s possibilities and sweet stuff, acceptance of his dignity, creation of conditions of self-knowledge and self-actualization for every individual.